Some Thoughts About Genre in Old Javanese Literature - Peter John Worsley (Jumantara: Jurnal Manuskrip Nusantara, 2021)
Robson in 1983 and 1988 in his reconsideration of the poetics of kakawin epics and Javanese philology drew readers’ attention to the importance of genre for the history of ancient Javanese literature. Aoyama in his study of the kakawin Sutasoma in 1992, making judicious use of Hans Jauss’s concept of “horizon of expectation”, offered the first systematic discussion of the genre of Old Javanese literary works. The present essay offers a commentary on the terms which mpu Monaguna and mpu Prapañca, authors of the thirteenth century epic kakawin Sumanasāntaka and the fourteenth century Deśawarṇana, themselves, employ to refer to the generic characteristics of their poems. Mpu Monaguna referred to his epic poem as a narrative work (kathā), written in a prakṛt, Old Javanese, and rendered in the poetic form of a kakawin and finally as a ritual act intended to enable the poet to achieve apotheosis with his tutelary deity and his poem to be the means of transforming the world, in particular to ensure the wellbeing of the readers, listeners, copyists and those who possessed copies of his poetic work. Mpu Prapañca described his Deśawarṇana differently. Also written in Old Javanese and in the poetic form of a kakawin—he refers to his work variously as a narrative work (kathā), a chronicle (śakakāla or śakābda), a praise poem (kastawan) and also as a ritual act designed to enable the author in an ecstatic state of rapture (alangö), and filled with the power and omniscience of his tutelary deity, to ensure the continued prosperity of the realm of Majapahit and to secure the rule of his king Rājasanagara. The essay considers each of these literary categories.